2006
DOI: 10.3140/bull.geosci.2006.02.123
|View full text |Cite
|
Sign up to set email alerts
|

Stromatactis cavities in sediments and the role of coarse-grained accessories

Abstract: The analysis of previous experimental work made on the simulation of stromatactis-like cavities in rapidly settling suspensions of particulate matter substantiates the continuation of experiments toward identifying the conditions of cavity formation. It has been suggested that the most promising directions in this experimental work involve the simplification of complex factors (e.g., variables that derive from the properties of particles and media, as well as the sedimentation dynamics of slurries). Our new hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The presence of stromatactis in mud mounds formed beneath the storm-wave base, as described by Matyszkiewicz (1993), Krause (2001), and Boulvain et al (2004), suggests that internal erosion of sediments caused by migrating waters is not a decisive factor in the formation of stromatactis. Recently a new sedimentary hypothesis of stromatactis origin has been presented by Hladil (2005Hladil ( , 2007 and Hladil et al (2006) who suggested that these structures originated during turbulent deposition and separation of highly unsorted clastic material from strongly dispersed suspension cloud.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of stromatactis in mud mounds formed beneath the storm-wave base, as described by Matyszkiewicz (1993), Krause (2001), and Boulvain et al (2004), suggests that internal erosion of sediments caused by migrating waters is not a decisive factor in the formation of stromatactis. Recently a new sedimentary hypothesis of stromatactis origin has been presented by Hladil (2005Hladil ( , 2007 and Hladil et al (2006) who suggested that these structures originated during turbulent deposition and separation of highly unsorted clastic material from strongly dispersed suspension cloud.…”
Section: Introductionmentioning
confidence: 99%
“…The stromatactis limestone lies directly on truncated rocks. The surface of this limestone was again truncated and covered by a scatter of debris (Hladil et al 2006b). Crinoidal debris deposited in thin lenses or spray was delivered by storm flooding from the outer areas, locally from the E. Above these anomalous beds, the upper part of the E-MF consists of thin grainstone layers and algal bindstones.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, they are not completely absent, but they are minimized, due to absence of typical large scale or wide ramp environments. This change of knowledge regarding Moravian stromatactis was caused by recognition of the localization of cm-sized stromatactis in limestone lenses along the damaged reef margins of mid-E-MF times (J. Otava, Svážná studna; Hladil et al 2006b;Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such open spaces might have formed at the contacts of loose particles (ooids, oncoids, bioclasts, or intraclasts) and partly lithified microbial crusts during sedimentation (cf. Hladil et al 2006). According to Schmid et al (2001), the presence of small-scale discontinuities within sediment together with an unstable shelf position may led to gravitational slumping.…”
Section: Ft 3: Oolitic-bioclastic Limestonementioning
confidence: 99%